Microeconomic Implications of Remittances in an Overlapping Generations Model with Altruism and Self-Interest - Melkonyan, Tigran (IMF Working Papers; Working Paper ;, 2008)
The paper explicitly models the dynamic strategic aspects of the interaction between the migrant and the remittance-receiving relative(s), with the migrant behaving as a Stackelberg leader. It is also different from other formalizations of remittance behavior in its treatment of the two parties' interaction to realize potential gains from exchange. We demonstrate that when the migrant and the relative(s) cooperate to maximize the joint utility of the household, this leads to higher level of remittances as well as investment and hours worked by the relative(s). We use data from Armenia to test our predictions regarding implications of remittances flows on behavior of receiving households. Consistent with our predictions, remittance-receiving households work fewer hours and spend less on the education of their children. While saving more, these households are not leveraging their savings to borrow from the banking system to expand their business activities. This evidence suggests that the benefits of remittances might be overstated and emphasizes the importance of measuring their impact in a general- rather than a partial-equilibrium context.